An Empirical Assessment of Savings - Growth Nexus in India - Budhedeo, Shradha Hitesh (Indian Journal of Finance, 2015)
The behaviour of savings and economic growth in India has been puzzling. Savings rates have been progressively rising and have been impressive throughout the planned economic period. In contrast, the growth rates have been increasing slowly and are unpredictably low. Economic growth has failed to keep pace with the high savings rates in the economy. Upward sailing savings rates are often paralleled with sharp dips in growth rates. Hence, the progress of savings rates does not get reflected in the growth scenario. This phenomenon of 'high savings and low growth' made it imperative to investigate the nature and direction of causal influence between savings and growth in India. Hence, there was a need to empirically explore whether saving causes growth, or growth leads to savings, or if there was a bi-directional causal relationship between saving and growth, or did they really share any relationship at all. An examination of the causality issue between saving and growth would enable policymakers to devise such economic policies as may be fruitful in meeting the planned targets. This study examined the association between savings and economic growth in India over the planned economic era from 1950-2013 by engaging Granger causality (VECM) estimation technique using the cointegration approach. The empirical results indicated a bi-directional mutual causality between saving and income (both total and non-agricultural income) in the short-run. In the long-run, nominal national income Granger caused gross domestic savings uni-directionally, but savings shared a two-way causal relationship with nominal non-agricultural income.